Sports bra tightness affects respiratory muscle fatigue, breathing pattern, and perceptual responses during running - Harbour, E.; Farlock, R.; Marko, D.; Bahenský, P.; Schwameder, H. (Journal of Sports Sciences, 2025)
Elite female athletes are vulnerable to respiratory limitations, and sports bra tightness may contribute to this phenomenon. Since the underband is located over the diaphragmatic ribcage, its tightness may affect ribcage mechanics, breathing muscles coordination, and fatigue. Seventeen trained junior female runners (VO2max = 53 ± 4 mL/kg/min) ran on a treadmill at personal race pace until exhaustion (range 15-30 min) in three standardised underband tightnesses. Ventilation (VE) and breathing pattern were recorded via Opto-electronic plethysmography throughout the run. Spirometry, maximum inspiratory pressure (MIP), and leg and breathing effort questionnaires were collected pre- and post-run. MIP decreased more with the tight (-9.8 ± 8.3%) than the loose underband (-1.1 ± 7.3%) (p = 0.002). With greater underband tightness, VE was increased (+8.4 ± 13.1 % tight vs. loose, p = 0.03), inspiratory capacity was repressed (4.2 ± 5.1 %, p = 0.03) and thoraco-abdominal coordination was altered with earlier abdominal breathing sequencing. Since reduced underband tightness may be advantageous for ventilation via attenuated diaphragm fatigue, sports bras might be improved with updated fitting procedures or novel garment designs.